Rancang Bangun Game Edukasi 3D Rancang Bangun Game Edukasi 3D "Ucul Si Pejuang Covid" - Hanni, Yohanes; Kembuan, Olivia; Kumajas, Sondy (JOINTER : Journal of Informatics Engineering, 2023)
The Covid-19 what is usually known as the Corona virus, is a very dangerous virus which has killed thousands and even more people every day. One of the simple ways to fight this virus is to wear a mask when you are out of the house. This study aims to design a 3D game that can educate children about the importance of masks during the current pandemic. There are also several quizzes related to Covid-19 in this game. Not only quizzes that educate about Covid-19, there are also several math quizzes that are expected to hone the user's numeracy skills. This game has gameplay that is not difficult and easy to understand for children and adults, considering that the target users of this game are children aged 8 to 12 years who are still too new to understand prevention methods Covid-19 during this pandemic. The research method used in this study is the MDLC (Multimedia Development Life Cycle) method. The results of this study is a 3D educational game application "Ucul Si Pejuang Covid" which can be run on a PC as a means of education for children.